Effect of honey supplementation with bee products on quality parameters and mineral composition - Adam Florkiewicz, Lesław Juszczak; Gałkowska, Anna Piotrowska, Robert Socha, Dorota (Emirates Journal of Food and Agriculture, 2019)
The aim of this work was to evaluate the influence of supplementation of multiflower honey with bee products on selected quality parameters and on mineral composition. Supplementation of honey with bee products slightly affected the water content; however, part of samples had slightly exceeded the allowed water content. Addition of individual bee products resulted in significant increases in the amount of insoluble solids, free acidity and conductivity. The greatest effect was observed for honeys with pollen or beebread, due to higher levels of supplementation of honey with these products. The addition of bee products had little effect on HMF content. Supplementation of honey with beebread resulted in lower glucose and fructose content. Honeys with bee products exhibited slightly higher sucrose content, while in three of the analyzed samples sucrose content exceeded the allowed for honey limit. Supplementation of honeys with pollen or beebread significantly influenced an increase in K, Ca, Mg, Fe, Zn and Mn contents.